Social Network Analysis for Water, Sanitation, and Hygiene (WASH): Application in Governance of Decentralized Wastewater Treatment in India Using a Novel Validation Methodology - Narayan, Abishek Sankara; Fischer, Manuel; Lüthi, Christoph (Frontiers in Environmental Science, 2020)
Social network analysis (SNA) is a versatile and increasingly popular methodological tool to understand structures of relationships between actors involved in governance situations. Given the complexity of the set of stakeholders involved in the governance of Water, Sanitation and Hygiene (WASH) and the diversity of their interests, this article introduces SNA to the WASH sector. The use of SNA as an appropriate diagnostic tool for Citywide Inclusive Sanitation is explored. Missing data is a major problem for SNA in the studies of governance situations, especially in low- and middle-income countries. Therefore, a novel validation methodology for incomplete SNA data, relying on information from internal and external experts is proposed. SNA and the validation method is then applied to study the governance of decentralized wastewater treatment in four cities of India. The results corroborate key differences between mega and secondary cities in terms of institutions, community engagement and overall sanitation situation including aspects of decentralised wastewater treatment plants, based on the city types.